Relationship between Trade Liberalisation, Economic Growth and Trade Balance: An Econometric Investigation - Ashok Parikh; Corneliu Stirbu (Hamburg Institute of International Economics (HWWA), 2004)
This is a study of 42 developing countries of Asia, Africa and Latin America in which we first examine the impact of trade liberalisation on economic growth, investment share of GDP, openness, trade balance and current accounts (as percentages of GDP). Both panel data and country by country data are used to measure the impact of liberalisation on domestic economic growth measured in PPP terms from the data available in Heston, Summers and Aten (2001) study. Domestic economic growth is often positively related to liberalisation for many countries of our sample. Next we analyse the impact of growth on trade balance and current account to examine whether higher economic growth due to liberalisation leads to adverse effect on balance of trade. Trade balance is normalised by GDP to take into consideration different sizes of countries. We also allow control variables in both sets of regressions such as terms of trade, advanced countries' growth rates, liberalisation and debt related variables. The balance of payments constrained growth model uses foreign exchange constraint that limits growth and using the Harrod multiplier, Thirlwall and Hussain derived a growth equation which is apparently constrained by balance of payments. We use this model in the first part as a behavioural equation and establish that liberalisation promotes growth and such output growth in pre-liberalisation period is lower than that in post- liberalisation period. Panel data of 42 countries, regional panel for three regions (fixed effect and random effect models) and country by country analysis (OLS regression) is conducted. These relationships suggest that liberalisation promotes growth but growth itself has negative effect on trade balance for a large majority of countries. This study uses the latest available data on real GDP, growth rates of individual and advanced countries and examines the relationship between liberalisation and growth, liberalisation and trade balance and also the impact of exchange rate or terms of trade policies on trade balance. One of the models in a cross-section regression study makes use of political and security variables and concludes that the convergence or ?catchingup? hypothesis is supported and extreme political repression tends to constrain growth. One unit change in liberalisation index leads on average to1.62 percentage point change in growth rates on average, ceteris paribus.
Keywords: C23; O24; F14; C21; F32; 330; liberalisation; trade balance; developing countries; panel data estimation; Aussenhandelsliberalisierung; Wirtschaftswachstum; Handelsbilanz; Zahlungsbilanzungleichgewicht; Schätzung; Entwicklungsländer